Os organismos, a sensibilidade e a origem das mentes. Conciliando Biologia e Psicologia - Lencastre, Marina Prieto Afonso (Trabalhos de Antropologia e Etnologia, 2020)
Part of the current debate on artificial intelligence questions whether consciousness is possible in the various digital formats. The present article answers this question focusing on the biological evolution of organisms, the differentiation of the nervous systems and the emergence of minds, stemming from the original organic sensibility. The intentionality of behaviors is conflated with the orientation of the minds, thus adjusting biology and psychology.